Intake of Trans Fatty Acid in Japanese University Students - KAWABATA, Terue; HAGIWARA, Chie; MIYAGI, Shigeji; SHIGEMITSU, Sachiko; SUGANO, Michihiro; SHINJO, Sumie; MARUYAMA, Takenori; ADACHI, Naoko (Journal of Nutritional Science and Vitaminology, 2010)
Because trans fatty acids (TFAs) are a potent risk factor for coronary heart disease, it is important to know the amount of TFA consumed. We estimated TFA intakes of Japanese university students by direct measurement. Subjects included 118 students (57 males and 61 females) in two regions of Japan: Kanto (Tokyo area) and Okinawa. A dietary survey was conducted over six consecutive days using dietary records and photographic records. A single-day meal in the survey period was reproduced to measure TFA content by gas chromatography. The median values of TFA intakes (and energy percentage) estimated by the contents of reproduced meals for men were 0.43 g/d (0.22%) in Kanto and 0.30 g/d (0.14%) in Okinawa. Corresponding values for women were 0.49 g/d (0.29%) and 0.73 g/d (0.35%), respectively. Compared to the group with a low TFA intake, the subjects with a high TFA intake consumed significantly more energy from total fat and saturated fatty acids, and had a high ratio of TFA/linoleic acid. In addition, multiple regression analysis showed the intakes of TFA were positively associated with those of saturated fatty acids and groups of nonessential groceries such as cookies, cakes and pastries. In conclusion, the TFA intakes of these survey subjects were relatively lower than the WHO recommended energy ratio (<1%). However, nutritional education on dietary habits seems indispensable for those subjects who are consuming high volumes of TFA.